18F-FDG PET/CT predicts microvascular invasion and early recurrence after liver resection for hepatocellular carcinoma: A prospective observational study. Issue 6 (June 2019) - Lim, Chetana; Salloum, Chady; Chalaye, Julia; Lahat, Eylon; Costentin, Charlotte E.; Osseis, Michael; Itti, Emmanuel; Feray, Cyrille; Azoulay, Daniel
Abstract: Background: This study assessed the prognostic value of 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) in the prediction of MVI and early recurrence following resection. Method: This prospective study (ClinicalTrials.gov ID: NCT02145013) included 78 consecutive HCC patients who underwent 18F-FDG PET/CT before curative-intent resection from 2014 to 2017. Prognostic factors available before surgery for predicting MVI and early recurrence (≤2 years) were identified by univariate and multivariate analyses. Results: The 18F-FDG PET/CT result was positive in 30 (38%) patients. MVI was present in 33% (26/78) of specimens. Early recurrence occurred in 19% (14/74) of surviving patients. PET/CT positivity was the sole independent predictor of MVI (odds ratio [OR] = 3.6, 95% confidence interval [CI] = 1.1–11.2; p = 0.03), with a specificity and sensitivity for predicting MVI of 73% and 62%, respectively. Analysis of variables available before surgery showed that PET/CT positivity (hazard ratio [HR] = 5.8, 95% CI = 1.6–20.4; p = 0.006) and the male sex (HR = 6.6; 95% CI = 1.8–24.2; p = 0.005) were independent predictors of early recurrence. Conclusion: 18F-FDG PET/CT predicts MVI and early recurrence after surgery for HCC and could be used to select patients for neoadjuvant treatment.